2010
DOI: 10.1007/s00268-010-0785-9
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting the Probability of Carcinoma in Patients with Intraductal Papillary‐Mucinous Neoplasm

Abstract: The nomogram has high diagnostic predictability for carcinoma in patients with IPMN and for individual cancer probability. This instrument may help to identify patients who need a surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…There were studies where the risk for malignancy was analyzed with several clinical findings including EUS, CT, and MRI. [18][19][20] Shimizu et al 18 in 2010 analyzed several clinical variables of 81 IPMNs including 56 BD-IPMNs and developed a nomogram that had a higher diagnostic predictability for carcinoma in patients with IPMN. It consisted of sex, types of lesion (BD-IPMN vs MD-IPMN), size, and cytology.…”
Section: Discussionmentioning
confidence: 99%
“…There were studies where the risk for malignancy was analyzed with several clinical findings including EUS, CT, and MRI. [18][19][20] Shimizu et al 18 in 2010 analyzed several clinical variables of 81 IPMNs including 56 BD-IPMNs and developed a nomogram that had a higher diagnostic predictability for carcinoma in patients with IPMN. It consisted of sex, types of lesion (BD-IPMN vs MD-IPMN), size, and cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent clinicopathological studies have shown that IPMNs arising in the main pancreatic duct (MPD) are more aggressive than those arising in the branch pancreatic duct (BPD), and the malignancy rate of main duct type IPMN has been reported to be 57% to 92%, [4][5][6]10 whereas that of branch duct type IPMN has been reported to be 6% to 58%. [10][11][12][13][14] Therefore, although most clinicians agree that surgical resection is required for all main duct type IPMNs, the management of branch duct type IPMNs remains controversial, because branch duct type IPMN generally has a low risk of malignancy.…”
mentioning
confidence: 99%
“…html) [36]. Genetic risk may differ by ethnicity or nationality, so that risk-assessment tools, such as a nomogram [37] based on multivariables, will be needed in the future for the Japanese population.…”
Section: Abbreviationsmentioning
confidence: 99%